Sowing of spring cereals in broad bands and the effect of sowing rate, rolling and irrigation on the results - Elonen, Paavo; Kara, Osmo; Autio, Leo (Agricultural and Food Science, 1972)
In 1971 two large field experiments, one for spring wheat and the other for barley, were carried out on silty clay soil in southern Finland. Three sowing methods were compared at three sowing rate levels (wheat: 140, 275 or 400 kg/ha, barley: 100, 200 or 300 kg/ha), at two levels of rolling (not rolled or rolled by a Cambridge-roller, 330 kg/m), and at two levels of irrigation (not irrigated or irrigated twice in June, 30 mm at both times). Wheat produced 9 ± 2 % higher grain yields sown with a 12.5 cm spacing between coulters in 7 cm bands than in rows of 2 cm. The increases in yield were almost equal irrespective of the seeding rate, rolling or irrigation. The sowing methods had no noteworthy influence on the ripening or the weight of the wheat grains. Barley responded to the sowing methods to a lesser extent than did wheat. Bands 7 cm wide with 12.5 cm spacing resulted in 5 ± 2 % higher wheat yields and 2 ± 1 % higher barley yields than did bands 10 cm wide with 25 cm spacing. The results indicate that the band method with relatively small spacings between the bands is worth further and more detailed study. An increase in the seeding rate from low to »normal» increased the yields, speeded up ripening and decreased the weight of grains, but when normal seeding rates were exceeded the grain yields were not further improved. Rolling speeded up ripening but did not significantly increase the grain yields. Of the factors included in the study, the sprinkler irrigation affected the yields most by increasing the grain yields of wheat by 23 ± 22 % and those of barley by 29 ± 9 %.